The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.37358/rc.19.2.6919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Capacities and Phenols Composition of Wild and Cultivated Berries

Abstract: The study presents original results concerning analytical characterization of alcoholic extracts of four wild berries (blueberries, blackberries, red currants and raspberries) and two cultivated berries (black cherries and strawberries). Total and some individual phenols concentrations were determined using molecular absorption spectrometry (modified Folin Ciocalteu method) and HPLC-DAD technique. The measurement of lipid-soluble antioxidant capacity (ACL) was done by photochemiluminescence method using trolox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Identification and quantitative determination of the active constituents from samples macerates was done by comparing the chromatogram of standards mixture. The total phenols were estimated according to the Folin-Ciocalteau method [22][23][24][25][26][27][28].…”
Section: Identification and Quantification Of Phenolic Compounds By Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification and quantitative determination of the active constituents from samples macerates was done by comparing the chromatogram of standards mixture. The total phenols were estimated according to the Folin-Ciocalteau method [22][23][24][25][26][27][28].…”
Section: Identification and Quantification Of Phenolic Compounds By Hmentioning
confidence: 99%
“…The antioxidant capacity was evaluated using DPPH Radical Scavenging test. Gallic acid (GA) was used as standard to plot calibration curves and the results were expressed as equivalents (mg GAE) [14,16,[27][28][29][30][31][32]. In 25 mL calibrated flasks different volume of gallic acid solutions were added, then 5 mL DPPH 0.063% (1.268 mM) in methanol, filled up to the mark with methanol and let in the dark, to the room temperature for 45 minutes before the absorbance registration at 530 nm versus methanol.…”
Section: Dpph Radical Scavenging Testmentioning
confidence: 99%
“…The Black Sea is a great resource due to its geographical position in relation to the planetary Ocean, the character of semi-closed, a huge catchment area, as well as its unique hydro-biological features make the Black Sea a highly sensitive ecosystem, exposed to pollution [1]. Changes in the parameters of the physical, chemical and biological agents of the Black Sea is due to the anthropic impact on the entire basin, and eutrophication is hastened by the vast quantities of biogenic sources offered by the Danube, the Dnieper and the Dniester [2,3]. With increasing human population, pollution has become a great concern.…”
mentioning
confidence: 99%
“…Okan et al (2018) have found that the content of phenolic compounds and flavonoids in 28 varieties of blueberries from Turkey varied in the range 76.20-215.12 mg GAE/100g FW and 30.44-91.69 mg quercetin/100g FW, respectively. Stanciu et al (2019) analyzed some berries (blueberry, raspberry, blackberry and red currant) and showed that the highest total phenolic content was registered for blueberries (543.50 mg GAE/100g FW), followed by red currants (432.30 mg GAE/100gFW), blackberries (425.00 mg GAE/100gFW), and raspberries (344.50 mg GAE/100gFW).…”
Section: Total Phenolics Flavonoids and Anthocyaninsmentioning
confidence: 99%